L’Union soviétique et les minerais stratégiques : Erreurs et vérités - Rezun, Miron (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1987)
This is an analysis of the major strategic minerals (sometimes called strategic materials), including some of the precious metals, which are vital to the Western economies. It focuses primarily on Soviet strategic minerals policies and examines the conflicting hypotheses for and against a resource war waged by the Soviet Union. The conclusions reached on the strength of the evidence so far is that Soviet policies have been chiefly economic and motivated by economic self-interest ; the Soviet Union is seen as an eager competitor for markets to acquire hard currency and not as a power eager to deprive the West of critical resources. A case is also made for the increasing importance of materials science, ocean mining and substitution, which is likely to make the West, including the USSR, invulnerable to supply disruptions in the future.